Blast resistant materials concrete and glass - Mohammed Alias Yusof; Norazman Mohamad Nor; Ariffin Ismail (Penerbit UPNM, 2018)
Blast resistant materials book presents the basic knowledge and technologies used in the engineering of explosive and development of blast resistant materials. In this book explains the explosive, blast phenomena, field blast testing procedures, fibres in concrete, materials for blast resistant concrete and glass with relevant testing standard for blast resistant materials